CULTURE AND PRAGMATICS IN LANGUAGE TEACHING - Mamarajabov Davlatbek; Feruza Kholbekova (Ustozlar uchun, 2025)
This article analyzes the interrelation between culture and pragmatics in foreign language teaching and their essential role in shaping learners’ communicative competence. It explores the types of pragmatic failures caused by cultural differences and offers strategies to prevent such errors. Through practical examples, research insights, and methodological suggestions, the study highlights the real-world importance of teaching cultural sensitivity alongside linguistic proficiency.